PUBLIC RELATIONS MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION IN ISLAMIC BOARDING SCHOOLS - Jufaini, Jufaini (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to analyze the role and contribution of public relations management in the development of educational institutions in Islamic boarding schools. The focus of this research is to identify factors that influence the effectiveness of public relations management, evaluate the use of social media in disseminating information and building relationships with stakeholders, and assessing the importance of regular evaluations in public relations strategies. This research uses a qualitative approach with a case study type of research. Data collection techniques include in-depth interviews, participant observation, and document analysis. Data analysis was carried out using the Miles and Huberman interactive analysis model. The research results show that public relations management at Islamic boarding schools plays a major role in building harmonious relationships with the community, student guardians and alumni. The division of public relations duties into two external and internal public relations divisions supports communication efficiency and increases support from stakeholders. The implications of this research emphasize the importance of a structured and sustainable public relations management strategy in Islamic educational institutions. This research makes an important contribution in understanding the role of public relations management and can be a model for other educational institutions in building strong relationships with the community.